BUDAYA NUSANTARA MELALUI DAMAR KURUNG : Analisis Bahasa Rupa - ismoerdjahwati, ika (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Culture is a culture of Nusantara Indonesian , which owns various cultures scattered throughout the islands , is highly variable and shifting orientation into the craft industry . In contemporary culture, the culture industry has experienced ‘ globalization. So some of the work of cultural products,which could not be untouched by globalization, becoming increasingly marginalized and not recognized, even then becoming more and more lost. Prior to all of that , then comes the initiativeto conduct a study of the works of cultural products fared thus , among others , lanterns Damarkurung of Gresik, by Masmundari (late) . Research using qualitative research paradigm constructivist.Through this research is expected to gain an understanding of the images contained on the rounded wall paper lanterns, its origin, its artists, and its supporting environment. The conclusionis, the pictures turned out to have the intent and purpose, as well as the old concept of how the reading of the temples in East Java, which is used to guide how to draw and how to tell the images that surround the lantern.